High-barrier light-proof MDOPE sterile packaging bag and preparation method thereof

Through the composite technology of aluminum-plated MDOPE film and polyvinyl alcohol film, the problem of difficulty in achieving high barrier, antibacterial and light-proof performance at the same time in existing packaging materials is solved, and efficient gas barrier, antibacterial and light-proofing effects are achieved, ensuring food safety and extended shelf life.

CN119610831AInactive Publication Date: 2025-03-14ZHEJIANG SUPER STAR PACKAGING MATERIAL CO LTD

Patent Information

Application Number
CN202510142921.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-10
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing packaging materials are difficult to achieve high barrier properties, antibacterial properties and light protection at the same time, and cannot meet the needs of food safety and extended shelf life.

Method used

By combining the aluminum-plated MDOPE film with the polyvinyl alcohol film, the high-barrier light-proof MDOPE aseptic packaging bag is prepared by using the light barrier and moisture-proof properties of the aluminum-plated MDOPE film, combined with the gas barrier and antibacterial properties of the polyvinyl alcohol film.

Benefits of technology

It achieves efficient barriers to polar and non-polar gases, enhances the antibacterial properties of packaging bags, and provides light-proof effects through aluminum plating, effectively protects food safety and extends shelf life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention belongs to the technical field of packaging materials, and particularly relates to a high-barrier light-proof MDOPE sterile packaging bag and a preparation method thereof. The high-barrier light-proof MDOPE sterile packaging bag is formed by compounding an aluminum-plated MDOPE film and a polyvinyl alcohol film, the polyvinyl alcohol film is prepared from raw materials including polyvinyl alcohol, organic montmorillonite and a cross-linking agent, the aluminum-plated MDOPE film is obtained by longitudinally stretching a PE film through MDO and plating aluminum, and the prepared packaging bag has good barrier property, antibacterial property and mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of packaging materials, and in particular relates to a high-barrier light-proof MDOPE aseptic packaging bag and a preparation method thereof. Background Art

[0002] The rapid development of modern commerce and logistics industries has promoted the progress of the global packaging industry. Packaging needs to be able to maintain the stability of the internal environment, protect the quality or performance of the packaged objects and extend their shelf life, especially packaging materials for food, medicine, electronic components, military supplies and other products, which require packaging materials to have good barrier properties. Barrier property refers to the ability of a material to prevent oxygen, water vapor, organic gas, light, heat and other penetrating objects from the high concentration side through the barrier material to the low concentration side. When polymer materials are used as barrier materials to block gas or vapor molecules, due to the concentration difference on both sides, gas or solvent vapor molecules can penetrate through the polymer materials under the action of this driving force. Common high barrier materials include polyvinylidene chloride, copolymers of ethylene and vinyl alcohol, polyvinyl alcohol, nylon, nitrile resins, etc. Although a single polymer barrier material has good barrier properties, it still cannot meet the market's requirements for barrier materials with higher barrier performance / price ratio.

[0003] The Chinese patent with publication number CN117601529A discloses a high barrier degradable polyethylene composite film, bag and preparation method, which is obtained by compounding a degradable polyethylene printed film and a high barrier polyethylene heat-sealing film. By strictly controlling the raw materials for the preparation of the three layers of the degradable polyethylene printed film and the high barrier polyethylene heat-sealing film, it is ensured that the degradable polyethylene printed film and the high barrier polyethylene heat-sealing film have high mechanical properties and transparency. At the same time, the degradable polyethylene printed film has excellent printing performance, high ink layer bonding fastness and good barrier performance; the Chinese patent with publication number CN117601529A discloses a high barrier degradable polyethylene composite film, bag and preparation method, which is obtained by compounding a degradable polyethylene printed film and a high barrier polyethylene heat-sealing film. By strictly controlling the raw materials for the preparation of the three layers of the degradable polyethylene printed film and the high barrier polyethylene heat-sealing film, it is ensured that the degradable polyethylene printed film and the high barrier polyethylene heat-sealing film have high mechanical properties and transparency. At the same time, the degradable polyethylene printed film has excellent printing performance, high ink layer bonding fastness and good barrier performance; Chinese patent N117801456A discloses a high barrier and tensile resistant composite material and packaging bag, which is prepared from polyethylene terephthalate, polyvinylidene chloride, aminopropyl triethoxysilane, trimesoyl chloride, cellulose acetate, chitosan, maleic anhydride and NN dimethylamide as raw materials. The barrier capacity is improved by grafting polyethylene terephthalate, polyvinylidene chloride, NN dimethylamide and maleic anhydride. The addition of trimesoyl chloride and cellulose acetate greatly enhances its tensile resistance and high temperature resistance. However, as people pay more attention to their health and the requirements for food quality continue to increase, the preparation of packaging bags with good barrier and antibacterial properties to ensure food safety and extend the shelf life of food has become a research focus. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a high-barrier light-proof MDOPE sterile packaging bag and a preparation method thereof, which is obtained by compounding an aluminum-plated MDOPE film and a polyvinyl alcohol film. The prepared packaging bag has good barrier and antibacterial properties.

[0005] The technical solution provided by the present invention to solve the above technical problems is as follows: A high-barrier light-proof MDOPE sterile packaging bag, wherein the high-barrier light-proof MDOPE sterile packaging bag is composited with an aluminized MDOPE film and a polyvinyl alcohol film; The polyvinyl alcohol film is made of the following raw materials in parts by weight: 70-90 parts of polyvinyl alcohol, 18-28 parts of organic montmorillonite, and 8-13 parts of a cross-linking agent; The aluminum-plated MDOPE film is obtained by longitudinally stretching a PE film through MDO and then aluminum-plating the film.

[0006] Furthermore, the preparation process of the organic montmorillonite is as follows: S1. Add sodium montmorillonite to deionized water, raise the temperature to 45-65°C and stir for 4-6 hours to obtain a montmorillonite aqueous dispersion; wherein the mass fraction of the montmorillonite aqueous dispersion is 6%-9%; S2, add a long-chain quaternary ammonium salt to deionized water, raise the temperature to 75-85°C and stir for 2-4h to obtain a quaternary ammonium salt solution, mix the quaternary ammonium salt solution with the montmorillonite aqueous dispersion and stir at 45-65°C for 4-6h to obtain a mixed solution; wherein the concentration of the quaternary ammonium salt solution is 0.4%-0.8%; the long-chain quaternary ammonium salt is hexadecyltrimethylammonium bromide or octadecyltrimethylammonium chloride; S3. The mixed solution is filtered and separated under reduced pressure to obtain a crude organic montmorillonite product, and the crude organic montmorillonite product is washed with deionized water until no precipitate is generated when tested with an AgNO3 solution, and the filter cake is dried and crushed to obtain an organic montmorillonite modified with a long-chain quaternary ammonium salt.

[0007] Montmorillonite is a type of negatively charged silicate sheet with an aluminum oxide octahedral structure and a large ion exchange capacity. Sodium-based montmorillonite is a two-dimensional layered inorganic nanomaterial obtained by inorganically modifying natural montmorillonite using the sodium modification method. It has a high aspect ratio and is composed of multiple homogeneous thin layers. It is blended with a polymer matrix and uses the "tortuous path" and "permeability area reduction" effects of small molecules entrained by the sheet filler to improve the gas barrier properties of the matrix and improve the mechanical properties of the composite. However, due to the presence of polar groups such as hydroxyl groups and inorganic ions between montmorillonite layers, it has a high surface energy, resulting in poor compatibility between montmorillonite and polymers, and is prone to agglomeration in the polymer matrix to form defects. Therefore, in this step, long-chain quaternary ammonium salt is used to carry out organic modification on sodium montmorillonite, and its ion exchange effect is used to graft and intercalate the organic chain segments into the sheets of sodium montmorillonite, thereby reducing the surface energy of sodium montmorillonite, facilitating the dispersion of sodium montmorillonite, and facilitating the mixing with the polymer matrix. At the same time, since quaternary ammonium salt can be adsorbed onto the surface of the bacterial cell, the lipid layer is inserted through the hydrophobic group, the permeability of the cell membrane is changed, the membrane structure is destroyed, and the leakage of intracellular substances is caused, so that the bacterial cell is dead, the introduction of long-chain quaternary ammonium salt can also improve the antibacterial properties of the film.

[0008] Furthermore, the preparation process of the polyvinyl alcohol film is as follows: A1. Mix the dried polyvinyl alcohol pellets with organic montmorillonite and add them into a twin-screw extruder for melt extrusion to prepare organic montmorillonite-modified polyvinyl alcohol masterbatch; wherein the drying conditions of the polyvinyl alcohol pellets are: drying at 60-80° C. in a vacuum drying oven for 4-6 hours; A2, heating and melting the organic montmorillonite modified polyvinyl alcohol masterbatch, adding dilute hydrochloric acid to mix evenly and adjusting the pH to 2, then adding a crosslinking agent thereto, after the crosslinking reaction for 2-4 hours, adding the mixture to a twin-screw extruder for extrusion to obtain a crosslinked modified polyvinyl alcohol masterbatch; wherein the crosslinking agent is citral; A3. Put the cross-linked modified polyvinyl alcohol masterbatch into a tablet press and prepare the polyvinyl alcohol film by hot pressing.

[0009] Polyvinyl alcohol is a water-soluble polymer material obtained by alcoholysis of polyvinyl acetate, and has excellent film-forming, bonding, emulsifying, mechanical strength and other properties. Polyvinyl alcohol has strong hydrophilicity because it contains a large number of hydroxyl groups. Under humid conditions, polyvinyl alcohol absorbs water and swells, and free water enters between the polyvinyl alcohol molecular chains, resulting in the weakening of hydrogen bonds between the polyvinyl alcohol hydroxyl groups, resulting in an increase in the free volume between molecules, which increases gas permeability and deteriorates gas barrier properties. Therefore, in this step, inorganic organic montmorillonite is used for filling. On the one hand, the lamellar structure of montmorillonite can make the gas permeation path more complicated. At the same time, the addition of montmorillonite makes it more difficult for the polyvinyl alcohol molecular chain to move. The stronger the constraint on the molecular chain, the more difficult it is for the molecular chain to move, the smaller the free volume in the polymer, and the stronger the barrier performance of the polymer; on the other hand, the various functional groups including hydroxyl groups contained on the surface of montmorillonite can produce hydrogen bonds with the hydroxyl groups on the polyvinyl alcohol molecular chain to form a cross-linked network, which blocks the penetration of small molecules through the network structure and improves the barrier performance of the material; the addition of organic montmorillonite can effectively improve the gas barrier property of polyvinyl alcohol, but because the hydrophilicity of polyvinyl alcohol has not been improved, its water vapor barrier performance is poor, so in this step, a cross-linking agent citral is introduced to perform cross-linking modification on it, and the hydrophilic free hydroxyl groups in polyvinyl alcohol can be effectively reduced by the aldehyde group of citral and the hydroxy acetal in polyvinyl alcohol, thereby improving the water resistance of polyvinyl alcohol; at the same time, citral has high antioxidant and antibacterial properties, and is safe, non-toxic, and green and environmentally friendly. The introduction of citral can further improve the overall gas barrier and antibacterial properties of the film.

[0010] Furthermore, the preparation process of the aluminized MDOPE film is as follows: polyethylene pellets are added to a twin-screw extruder for extrusion, then blown into a film bubble and then cooled, and then longitudinally stretched by MDO to obtain an MDOPE film; the MDOPE film is placed in an aluminizing chamber for vacuum aluminum plating to obtain the aluminized MDOPE film; wherein the heating temperature of the MDO longitudinal stretching is 90-100°C, and the stretching ratio is 1.2-2.4:1.

[0011] The aluminum-plated MDOPE film is covered with an aluminum layer on its surface, which prevents light from penetrating. Therefore, the items in the package can be protected from direct sunlight and ultraviolet rays, thereby better protecting the items. In addition, the aluminum-plated layer can effectively isolate air, water vapor, etc., and has good moisture-proof and anti-oxidation properties.

[0012] The present invention also provides a method for preparing a high-barrier light-proof MDOPE sterile packaging bag. The preparation method comprises the following steps: subjecting an aluminum-plated MDOPE film and a polyvinyl alcohol film to a composite process to obtain a high-barrier light-proof MDOPE sterile composite film, and subjecting the composite film to aging and bag making to obtain the high-barrier light-proof MDOPE sterile packaging bag.

[0013] Polyvinyl alcohol polymer molecular chains contain more polar groups. According to the principle of like dissolves like, polyvinyl alcohol easily absorbs polar molecules such as water vapor in the air, but non-polar gases such as hydrogen are difficult to diffuse and penetrate into it. Polyethylene is a non-polar thermoplastic polymer, and polar gases such as water vapor have low permeability in it. Therefore, the method of using polyvinyl alcohol film and aluminum-plated MDOPE film composite can simultaneously play a good barrier role for polar gas molecules and non-polar gas molecules. In addition, since the surface of the polyvinyl alcohol film contains a variety of oxygen-containing functional groups, during the composite process, it can form a chemical bond with the aluminum layer of the aluminum-plated MDOPE film, so that the two have a good bonding effect.

[0014] The present invention has the following beneficial effects: A high-barrier light-shielding packaging bag is prepared by compounding polyvinyl alcohol film and aluminum-coated MDOPE film. Polyvinyl alcohol is a polar polymer and polyethylene is a non-polar polymer. The two can be compounded to have a good barrier effect on both polar gas molecules and non-polar gas molecules.

[0015] When preparing polyvinyl alcohol film, inorganic organic montmorillonite is used for filling. On the one hand, the lamellar structure of montmorillonite can make the gas permeation path more complicated. At the same time, the addition of montmorillonite makes the movement of polyvinyl alcohol molecular chains more difficult, and the barrier performance is enhanced. On the other hand, the various functional groups including hydroxyl groups contained on the surface of montmorillonite can produce hydrogen bonds with the hydroxyl groups on the polyvinyl alcohol molecular chains to form a cross-linked network, which blocks the penetration of small molecules through the network structure and improves the barrier performance of the material. At the same time, citral is used to cross-link and modify polyvinyl alcohol, so that the overall gas barrier and antibacterial properties of the film are further enhanced.

[0016] The long-chain quaternary ammonium salt is used to organically modify the sodium montmorillonite. By utilizing its ion replacement effect, the organic chain segments are grafted and intercalated into the sheets of the sodium montmorillonite, which reduces the surface energy of the sodium montmorillonite, facilitates the dispersion of the sodium montmorillonite, facilitates the mixing with the polymer matrix, and improves the mechanical properties of the polymer matrix. At the same time, the introduction of the long-chain quaternary ammonium salt can also improve the antibacterial properties of the film. DETAILED DESCRIPTION

[0017] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0018] The polyvinyl alcohol (117 analytical grade) used in the present invention was purchased from Kuraray, Japan, sodium montmorillonite (high purity, >98%) was purchased from Nanocor, hexadecyltrimethylammonium bromide (high purity, >98%) and octadecyltrimethylammonium chloride (high purity, >98%) were purchased from Aladdin, citral (cis + trans 97%) was purchased from Sinopharm Chemical Reagent Co., Ltd., and polyethylene (BE0400) was purchased from Suzhou Fengjuan Plastic Raw Materials Co., Ltd. All raw materials and reagents are commercially available.

[0019] Embodiment 1 A high-barrier, light-proof MDOPE sterile packaging bag, which is composited by an aluminized MDOPE film and a polyvinyl alcohol film; the polyvinyl alcohol film is made of the following raw materials in parts by weight: 85 parts of polyvinyl alcohol, 22 parts of organic montmorillonite, and 10 parts of a cross-linking agent; the aluminized MDOPE film is obtained by longitudinally stretching a PE film through MDO and then aluminizing it.

[0020] Among them, the preparation process of organic montmorillonite is: S1. Add sodium montmorillonite to deionized water, raise the temperature to 55°C and stir for 5 hours to obtain a montmorillonite aqueous dispersion; wherein the mass fraction of the montmorillonite aqueous dispersion is 8%; and the CEC of the sodium montmorillonite used is 140 mmol / 100 g; S2, add a long-chain quaternary ammonium salt to deionized water, raise the temperature to 80°C and stir for 3 hours to obtain a quaternary ammonium salt solution, mix the quaternary ammonium salt solution with the montmorillonite aqueous dispersion and stir at 55°C for 5 hours to obtain a mixed solution; wherein the concentration of the quaternary ammonium salt solution is 0.6%; the long-chain quaternary ammonium salt is octadecyltrimethylammonium chloride; S3, the mixed solution is filtered under reduced pressure to obtain a crude organic montmorillonite product, the crude organic montmorillonite product is washed with deionized water to remove excess long-chain quaternary ammonium salt, until no precipitate is generated by AgNO3 solution inspection, the washed filter cake is dried in a vacuum drying oven at 85°C for 12h to constant weight, and then the filter cake is ball-milled by a planetary ball mill and sieved through a 400-mesh sieve to obtain an organic montmorillonite modified with a long-chain quaternary ammonium salt.

[0021] Among them, the preparation process of polyvinyl alcohol film is: A1. Mix 85 parts by weight of dried polyvinyl alcohol pellets and 22 parts by weight of organic montmorillonite and add them into a twin-screw extruder for melt extrusion to prepare organic montmorillonite-modified polyvinyl alcohol masterbatch; wherein the polyvinyl alcohol pellets are dried in a vacuum drying oven at 80° C. for 5 hours; A2, heating and melting the organic montmorillonite modified polyvinyl alcohol masterbatch, adding dilute hydrochloric acid to mix evenly and adjusting the pH to 2, then adding 10 parts by weight of a crosslinking agent citral, and after a crosslinking reaction for 3 hours, adding the mixture to a twin-screw extruder for extrusion to obtain a crosslinked modified polyvinyl alcohol masterbatch; A3. Put the cross-linked modified polyvinyl alcohol masterbatch into a tablet press, and prepare the polyvinyl alcohol film by hot pressing at 4 MPa for 2 minutes. The temperature of the upper laminate is 150°C, and the temperature of the lower laminate is 150°C.

[0022] The preparation process of the aluminum-plated MDOPE film is as follows: adding polyethylene pellets to a twin-screw extruder for melt extrusion, then blowing the film to form a bubble and then cooling it, and then longitudinally stretching it through MDO to obtain an MDOPE film; the extrusion speed of the extruder is 420±50Kg / h, the heating temperature of the die head is 190-200°C, the film bubble is formed by blowing, the blowing ratio is 2.6, the heating temperature of the MDO longitudinal stretching is 90°C, the stretching ratio is 1.5:1, and the thickness of the obtained MDOPE film is 28μm; Then, the MDOPE film is placed in an aluminum coating chamber for vacuum aluminum coating to obtain an aluminum-coated MDOPE film. During the vacuum aluminum coating process of the MDOPE film, the temperature of the aluminum coating chamber is 1300°C and the vacuum degree is 2×10 -2 Pa, the unwinding speed of the MDOPE film is 230m / min, the aluminum wire feeding speed is 0.6m / min, the aluminum wire purity is greater than 99.99%, and the thickness of the aluminum coating is 24nm; after the aluminum coating is completed, nitrogen is introduced into the aluminum coating chamber in stages, and nitrogen is first filled in to the nitrogen pressure of 900Pa. After maintaining for 10h, nitrogen is filled in again to the nitrogen pressure of 1400Pa, and maintained for 12h to obtain an aluminum-coated MDOPE film.

[0023] A method for preparing a high-barrier, light-proof MDOPE sterile packaging bag, comprising the following steps: compounding an aluminum-plated surface of an aluminum-plated MDOPE film with a polyvinyl alcohol film to obtain a high-barrier, light-proof MDOPE sterile composite film through a composite process; wherein the composite process of the aluminum-plated MDOPE film and the polyvinyl alcohol film is a dry composite, the oven temperature is 55°C, and the composite tension is 6.8kg; then, the high-barrier, light-proof MDOPE sterile composite film is placed in a 48°C oven for aging for 52 hours to obtain a high-barrier, light-proof MDOPE sterile packaging bag; the heat-sealing temperature is 125°C, the temperature fluctuation is controlled at ±1°C, each position of the bag is heat-sealed 4 times, and the bag-making speed is controlled at 60 knives / minute.

[0024] Embodiment 2 Compared with the first embodiment, this embodiment has the following differences: the polyvinyl alcohol film is made of raw materials including the following parts by weight: 70 parts of polyvinyl alcohol, 18 parts of organic montmorillonite, and 8 parts of a cross-linking agent; In the preparation process of organic montmorillonite: in step S1, sodium montmorillonite is added to deionized water, the temperature is increased to 45°C and stirred for 4 hours, and the mass fraction of the montmorillonite aqueous dispersion is 6%; in step S2, long-chain quaternary ammonium salt is added to deionized water, the temperature is increased to 75°C and stirred for 2 hours, and it is mixed with the montmorillonite aqueous dispersion and stirred at 45°C for 4 hours, and the concentration of the quaternary ammonium salt solution is 0.4%.

[0025] In the process of preparing polyvinyl alcohol film: in step A1, 70 parts by weight of dried polyvinyl alcohol pellets are mixed with 18 parts by weight of organic montmorillonite and then added to a twin-screw extruder, and the drying conditions of the polyvinyl alcohol pellets are: drying at 60°C in a vacuum drying oven for 4 hours; in step A2, the organic montmorillonite-modified polyvinyl alcohol masterbatch is heated and melted, and diluted hydrochloric acid is added to mix evenly to adjust the pH to 2, and then 8 parts by weight of a cross-linking agent citral is added thereto, and the cross-linking reaction is carried out for 2 hours; in step A3, the cross-linked modified polyvinyl alcohol masterbatch is placed in a tablet press, and the polyethylene film is prepared by hot pressing at 3MPa for 2 minutes, and the temperature of the upper laminate is 140°C and the temperature of the lower laminate is 140°C.

[0026] In the preparation process of aluminized MDOPE film: the blowing ratio is 2.8, the stretching ratio is 1.8:1, and the thickness of the prepared MDOPE film is 26μm; in the aluminizing process of MDOPE film, the unwinding speed of MDOPE film is 220m / min, the aluminum wire feeding speed is 0.6m / min, and the thickness of the aluminum coating layer is 26nm; During the preparation process of the high-barrier light-proof MDOPE sterile packaging bag: the oven temperature is 50°C and the composite tension is 6.6kg during the composite process of the aluminized MDOPE film and the polyvinyl alcohol film; the high-barrier light-proof MDOPE sterile composite film is placed in a 45°C oven for aging for 48 hours to obtain a high-barrier light-proof MDOPE sterile packaging bag; the heat sealing temperature is 120°C, the temperature fluctuation is controlled at ±1°C, each position of the bag is heat-sealed 3 times, and the bag making speed is controlled at 60 knives / minute.

[0027] Embodiment 3 Compared with the first embodiment, this embodiment has the following differences: the polyvinyl alcohol film is made of raw materials including the following parts by weight: 90 parts of polyvinyl alcohol, 28 parts of organic montmorillonite, and 13 parts of a cross-linking agent; In the preparation process of organic montmorillonite: in step S1, sodium montmorillonite is added to deionized water, the temperature is increased to 65°C and stirred for 6 hours, and the mass fraction of the montmorillonite aqueous dispersion is 9%; in step S2, long-chain quaternary ammonium salt is added to deionized water, the temperature is increased to 85°C and stirred for 4 hours, and it is mixed with the montmorillonite aqueous dispersion and stirred at 65°C for 6 hours, and the concentration of the quaternary ammonium salt solution is 0.8%.

[0028] In the process of preparing polyvinyl alcohol film: in step A1, 90 parts by weight of dried polyvinyl alcohol pellets are mixed with 28 parts by weight of organic montmorillonite and then added to a twin-screw extruder, and the drying conditions of the polyvinyl alcohol pellets are: drying at 80°C in a vacuum drying oven for 6 hours; in step A2, the organic montmorillonite-modified polyvinyl alcohol masterbatch is heated and melted, and diluted hydrochloric acid is added and mixed evenly to adjust the pH to 2, and then 13 parts by weight of a cross-linking agent citral is added thereto, and the cross-linking reaction is carried out for 4 hours; in step A3, the cross-linked modified polyvinyl alcohol masterbatch is placed in a tablet press, and the polyethylene film is prepared by hot pressing at 5 MPa for 2 minutes, and the temperature of the upper laminate is 150°C and the temperature of the lower laminate is 150°C.

[0029] In the preparation process of aluminized MDOPE film: the blowing ratio is 2.4, the stretching ratio is 1.6:1, and the thickness of the prepared MDOPE film is 27μm; in the aluminizing process of MDOPE film, the unwinding speed of MDOPE film is 220m / min, the aluminum wire feeding speed is 0.8m / min, and the thickness of the aluminized layer is 28nm; During the preparation process of high-barrier light-proof MDOPE sterile packaging bags: the oven temperature is 60°C and the composite tension is 7kg during the composite process of the aluminized MDOPE film and the polyvinyl alcohol film; the high-barrier light-proof MDOPE sterile composite film is placed in a 50°C oven for aging for 48 hours to obtain high-barrier light-proof MDOPE sterile packaging bags; the heat sealing temperature is 125°C, the temperature fluctuation is controlled at ±1°C, each position of the bag is heat-sealed 5 times, and the bag making speed is controlled at 62 knives / minute.

[0030] Comparative Example 1 Compared with Example 1, in the preparation process of organic montmorillonite, in step S2, the long-chain quaternary ammonium salt is replaced by hexadecyltrimethylammonium bromide from octadecyltrimethylammonium chloride, and the rest is the same as Example 1.

[0031] Comparative Example 2 Compared with Example 1, in the preparation process of organic montmorillonite, in step S2, the long-chain quaternary ammonium salt is replaced with a silane coupling agent γ-aminopropyltriethoxysilane, and the rest is the same as Example 1.

[0032] Comparative Example 3 Compared with Example 1, the montmorillonite is not organically modified, and the rest is as described in Example 1, specifically: Among them, the preparation process of polyvinyl alcohol film is: A1. Mix 85 parts by weight of dried polyvinyl alcohol pellets and 22 parts by weight of montmorillonite and add them into a twin-screw extruder for melt extrusion to prepare montmorillonite-modified polyvinyl alcohol masterbatch; wherein the polyvinyl alcohol pellets are dried in a vacuum drying oven at 80° C. for 5 h; A2, heating and melting the montmorillonite modified polyvinyl alcohol masterbatch, adding dilute hydrochloric acid and mixing evenly to adjust the pH to 2, then adding 10 parts by weight of a crosslinking agent citral, and after a crosslinking reaction for 3 hours, adding the mixture to a twin-screw extruder for extrusion to obtain a crosslinked modified polyvinyl alcohol masterbatch; A3. Put the cross-linked modified polyvinyl alcohol masterbatch into a tablet press, and prepare the polyvinyl alcohol film by hot pressing at 4 MPa for 2 minutes. The temperature of the upper laminate is 150°C, and the temperature of the lower laminate is 150°C.

[0033] The rest is as per Example 1.

[0034] Comparative Example 4 Compared with Example 1, in the process of preparing the polyvinyl alcohol film, no crosslinking agent is added for crosslinking reaction, and the rest is referred to Example 1, specifically: The preparation process of polyvinyl alcohol film is as follows: A1. Mix 85 parts by weight of dried polyvinyl alcohol pellets and 22 parts by weight of organic montmorillonite and add them into a twin-screw extruder for melt extrusion to prepare organic montmorillonite-modified polyvinyl alcohol masterbatch; wherein the polyvinyl alcohol pellets are dried in a vacuum drying oven at 80° C. for 5 hours; A2. The obtained organic montmorillonite-modified polyvinyl alcohol masterbatch was placed into a tablet press, and the polyvinyl alcohol film was prepared by hot pressing at 4 MPa for 2 min. The temperature of the upper lamination plate was 150° C., and the temperature of the lower lamination plate was 150° C.

[0035] The rest is as per Example 1.

[0036] Comparative Example 5 Compared with Example 1, the polyvinyl alcohol film is not modified, and the rest is referred to Example 1, specifically: The preparation process of the polyvinyl alcohol film is as follows: 85 parts by weight of dried polyvinyl alcohol pellets are placed in a tablet press, and the polyvinyl alcohol film is prepared by hot pressing at 4 MPa for 2 minutes. The temperature of the upper laminate is 150°C, and the temperature of the lower laminate is 150°C. The drying conditions of the polyvinyl alcohol pellets are as follows: drying at 80°C in a vacuum drying oven for 5 hours.

[0037] The rest is as per Example 1.

[0038] The samples prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were subjected to relevant tests: Hydrophobicity test: The hydrophobicity test was performed on the polyvinyl alcohol side of the samples prepared in Examples 1 to 3 and Comparative Examples 1 to 5 using a contact angle meter; Barrier property test: The samples prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were subjected to barrier property tests. The oxygen permeability test was conducted according to the method in the national standard GB / T 1038-2022 "Test method for gas permeability of plastic films and sheets". The water vapor permeability test was conducted according to the method in the national standard GBT 1037-2021 "Determination of water vapor permeability of plastic films and sheets by cup weight gain and weight loss method". Antibacterial test: The antibacterial test was carried out on the polyvinyl alcohol side of the samples prepared in Examples 1 to 3 and Comparative Examples 1 to 5, and the test was carried out in accordance with QB / T2591-2003 "Antibacterial Plastics - Antibacterial Performance Test Method and Antibacterial Effect", and the test bacteria was ATCC27734 Staphylococcus aureus.

[0039] The above test results are shown in Table 1.

[0040] Table 1 Hydrophobicity, barrier properties and antibacterial properties test results It can be seen from the above test results that the polyvinyl alcohol side of the samples prepared in Examples 1 to 3 and Comparative Examples 1 to 3 has good hydrophobic properties, but the polyvinyl alcohol side of Comparative Examples 4 and 5 is hydrophilic. This is because after cross-linking modification with citral, the aldehyde groups contained in citral react with the hydroxyl groups contained in polyvinyl alcohol to reduce the hydrophilic free hydroxyl groups in polyvinyl alcohol, thereby improving the water resistance of polyvinyl alcohol. The oxygen permeability and water vapor permeability of Examples 1 to 3 are better than those of Comparative Examples 1 to 5, and in particular, Example 1 has the best barrier performance. It can be seen from the comparison between Comparative Example 1 (replacing the long-chain quaternary ammonium salt with octadecyl trimethyl ammonium chloride and hexadecyl trimethyl ammonium bromide) and Example 1 that, compared with hexadecyl trimethyl ammonium bromide, octadecyl trimethyl ammonium chloride has a longer molecular chain, which is more conducive to inserting into the montmorillonite sheet when modifying montmorillonite, thereby improving the dispersibility of montmorillonite in the polymer matrix. It can be seen from the antibacterial test results that Examples 1 to 3 and Comparative Example 1 have good antibacterial properties. Comparative Example 2 (replacing the long-chain quaternary ammonium salt with a silane coupling agent γ-aminopropyl triethoxysilane), Comparative Example 3 (not organically modifying montmorillonite) and Comparative Example 4 (not performing a cross-linking reaction) and Example 1 that both modifying montmorillonite with a long-chain quaternary ammonium salt and cross-linking polyvinyl alcohol with citral can play an antibacterial role, and the two have a synergistic effect, and the combination of the two has a better antibacterial effect.

[0041] Mechanical properties test: Tensile strength: The samples prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were subjected to a tensile strength test in accordance with the national standard GB / T 13022-1991 “Test method for tensile properties of plastic films”; Tear strength: The samples prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were tested for tear strength, with reference to QB / T1130-1991 "Test method for right-angle tearing performance of plastics", with a tensile speed of 200 mm / min and a room temperature of 25°C; Elongation at break: The elongation at break of the samples prepared in Examples 1 to 3 and Comparative Examples 1 to 5 was tested with reference to GB / T1040.3-2006 “Determination of tensile properties of plastics Part 3: Films and sheets”.

[0042] The above test results are shown in Table 2.

[0043] Table 2 Mechanical properties test results From the above tests, it can be found that the comprehensive mechanical properties of Examples 1 to 3 are better than those of Comparative Examples 1 to 5, especially the best performance of Example 1. By comparing Comparative Example 3 (no organic modification of montmorillonite) and Comparative Example 5 (no modification of polyvinyl alcohol film) with Example 1, it can be seen that the introduction of montmorillonite as an inorganic particle can improve the mechanical properties of the film, and the modification of montmorillonite by using long-chain quaternary ammonium salt is helpful for the dispersion of montmorillonite, enhances its compatibility with the polymer matrix, and makes its mechanical properties reach the best.

[0044] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0045] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A high barrier light-proof MDOPE sterile packaging bag, characterized in that: The high-barrier light-proof MDOPE sterile packaging bag is composited with an aluminized MDOPE film and a polyvinyl alcohol film; The polyvinyl alcohol film is made of the following raw materials in parts by weight: 70-90 parts of polyvinyl alcohol, 18-28 parts of organic montmorillonite, and 8-13 parts of a cross-linking agent; The aluminum-plated MDOPE film is obtained by longitudinally stretching a PE film through MDO and then aluminum-plating the film.

2. The high barrier light-proof MDOPE sterile packaging bag according to claim 1, characterized in that: The preparation process of the organic montmorillonite is: S1. Add sodium montmorillonite to deionized water, raise the temperature to 45-65°C and stir for 4-6 hours to obtain a montmorillonite aqueous dispersion; S2, add a long-chain quaternary ammonium salt to deionized water, raise the temperature to 75-85°C and stir for 2-4 hours to obtain a quaternary ammonium salt solution, mix the quaternary ammonium salt solution with the montmorillonite aqueous dispersion, and stir at 45-65°C for 4-6 hours to obtain a mixed solution; S3. The mixed solution is filtered and separated under reduced pressure to obtain a crude organic montmorillonite product, and the crude organic montmorillonite product is washed with deionized water until no precipitate is generated when tested with an AgNO3 solution, and the filter cake is dried and crushed to obtain an organic montmorillonite modified with a long-chain quaternary ammonium salt.

3. The high barrier light-proof MDOPE sterile packaging bag according to claim 2, characterized in that: The long-chain quaternary ammonium salt is hexadecyltrimethylammonium bromide or octadecyltrimethylammonium chloride.

4. The high barrier light-proof MDOPE sterile packaging bag according to claim 1, characterized in that: The preparation process of the polyvinyl alcohol film is as follows: A1, mixing the dried polyvinyl alcohol pellets with organic montmorillonite and adding them into a twin-screw extruder for melt extrusion to prepare an organic montmorillonite-modified polyvinyl alcohol masterbatch; A2, heating and melting the organic montmorillonite modified polyvinyl alcohol masterbatch, adding dilute hydrochloric acid and mixing evenly, then adding a crosslinking agent thereto, after crosslinking reaction for 2-4 hours, adding it to a twin-screw extruder for extrusion to obtain a crosslinked modified polyvinyl alcohol masterbatch; A3. Put the cross-linked modified polyvinyl alcohol masterbatch into a tablet press and prepare the polyvinyl alcohol film by hot pressing.

5. The high barrier light-proof MDOPE sterile packaging bag according to claim 4, characterized in that: The cross-linking agent is citral.

6. The high barrier light-proof MDOPE sterile packaging bag according to claim 4, characterized in that: The drying conditions of the polyvinyl alcohol pellets are: drying at 60-80° C. in a vacuum drying oven for 4-6 hours.

7. The high barrier light-proof MDOPE sterile packaging bag according to claim 1, characterized in that: The preparation process of the aluminized MDOPE film is as follows: polyethylene pellets are added into a twin-screw extruder for extrusion, then blown into a film bubble and then cooled, and then longitudinally stretched by MDO to obtain an MDOPE film; the MDOPE film is placed in an aluminizing chamber for vacuum aluminizing to obtain the aluminized MDOPE film.

8. The high barrier light-proof MDOPE sterile packaging bag according to claim 7, characterized in that: The heating temperature for longitudinal stretching of MDO is 90-100°C, and the stretching ratio is 1.2-2.4:

1.

9. The method for preparing the high barrier light-proof MDOPE sterile packaging bag according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: subjecting an aluminum-plated MDOPE film and a polyvinyl alcohol film to a composite process to obtain a high-barrier light-proof MDOPE sterile composite film, and subjecting the composite film to aging and bag making to obtain the high-barrier light-proof MDOPE sterile packaging bag.

Citation Information

Patent Citations

  • High-barrier degradable polyethylene composite film, bag and preparation method

    CN117601529A

  • High-barrier tensile composite material and packaging bag

    CN117801456A

  • Modified degradable film material preparation method

    CN109897232A

  • Preparation method of montmorillonite-modified transformer insulation paper

    CN112111995A

  • Polyethylene single-material composite film, preparation method and application of polyethylene single-material composite film in high-barrier food packaging

    CN117124685A

Cited By

  • High-barrier-property antibacterial food packaging film and preparation method thereof

    CN120888152A